Gender Implications of UK Welfare Reform and Government Equality Duties: Evidence from Qualitative Studies - Fran Bennett; Sirin Sung (Oñati Socio-Legal Series)
The UK coalition government is bound by equality duties to have regard to the impact of its policies on various groups, including women. This article investigates how far this legislative commitment is influencing debates about current welfare reforms, especially plans for ‘universal credit’ (a new means-tested benefit). The authors draw on findings from recent studies of within-household distribution from a gender perspective, including their own qualitative research. A major aim of this research was to facilitate more nuanced analysis of the effects of welfare reforms in terms of gender roles and relationships within the household. This article therefore examines how far findings from qualitative studies, in conjunction with the key principles they develop for assessing the gender impact of welfare reforms, can be used to examine ‘universal credit’; and to what extent these influenced the UK government’s proposals and analysis in the light of its commitment to equality duties.